ВИДОВОЙ СОСТАВ ИХТИОФАУНЫ КАСПИЙСКОГО МОРЯ В ПРЕДЕЛАХ МАНГИСТАУСКОЙ ОБЛАСТИ РЕСПУБЛИКИ КАЗАХСТАН (ҚазҰУ хабаршысы. Экология сериясы, 2016)
The species composition of the Caspian fish fauna is presented, for waters of the Mangistau region . Fishes were collected during four-year State Ecological Assessment (2007- 2010). Gill nets and beam trawl were used, both in spring and autumn periods. Totally, 49 species of 21 genera and 8 families were caught. The list of the species is included, with Kazakh, Russian and Latin names.